Existence of solutions of functional differential inclusions. (1992) - Anguraj, A.; Balachandran, K.
Abstract : We prove the existence of solutions of a functional differential inclusion. By using the variation of parameters formula we convert the functional differential inclusion into an integral inclusion and prove the existence of a fixed point of the set-valued mapping with the help of the Kakutani-Bohnenblust-Karlin fixed point theorem.